Ionic mechanisms limiting cardiac repolarization reserve in humans compared to dogs. (30th August 2013) - Jost, Norbert; Virág, László; Comtois, Philippe; Ördög, Balázs; Szuts, Viktória; Seprényi, György; Bitay, Miklós; Kohajda, Zsófia; Koncz, István; Nagy, Norbert; Szél, Tamás; Magyar, János; et al.
Key points Cardiac repolarization, through which heart‐cells return to their resting state after having fired, is a delicate process, susceptible to disruption by common drugs and clinical conditions. Animal models, particularly the dog, are often used to study repolarization properties and responses to drugs, with the assumption that such findings are relevant to humans. However, little is known about the applicability of findings in animals to man. Here, we studied the contribution of various ion‐currents to cardiac repolarization in canine and human ventricle. Humans showed much greater repolarization‐impairing effects of drugs blocking the rapid delayed‐rectifier current IKr than dogs, because of lower repolarization‐reserve contributions from two other important repolarizing currents (the inward‐rectifier IK1 and slow delayed‐rectifier IKs). Our findings clarify differences in cardiac repolarization‐processes among species, highlighting the importance of caution when extrapolating results from animal models to man. Abstract The species‐specific determinants of repolarization are poorly understood. This study compared the contribution of various currents to cardiac repolarization in canine and human ventricle. Conventional microelectrode, whole‐cell patch‐clamp, molecular biological and mathematical modelling techniques were used. Selective IKr block (50–100 nmol l−1 dofetilide) lengthened AP duration at 90% of repolarization (APD90) >3‐fold more in human than dog, suggesting smaller repolarization reserve in humans. Selective IK1 block (10 μmol l−1 BaCl2) and IKs block (1 μmol l−1 HMR‐1556) increased APD90 more in canine than human right ventricular papillary muscle. Ion current measurements in isolated cardiomyocytes showed that IK1 and IKs densities were 3‐ and 4.5‐fold larger in dogs than humans, respectively. IKr density and kinetics were similar in human versus dog. ICa and Ito were respectively ∼30% larger and ∼29% smaller in human, and Na+–Ca2+ exchange current was comparable. Cardiac mRNA levels for the main IK1 ion channel subunit Kir2.1 and the IKs accessory subunit minK were significantly lower, but mRNA expression of ERG and KvLQT1 (IKr and IKsα‐subunits) were not significantly different, in human versus dog. Immunostaining suggested lower Kir2.1 and minK, and higher KvLQT1 protein expression in human versus canine cardiomyocytes. IK1 and IKs inhibition increased the APD‐prolonging effect of IKr block more in dog (by 56% and 49%, respectively) than human (34 and 16%), indicating that both currents contribute to increased repolarization reserve in the dog. A mathematical model incorporating observed human–canine ion current differences confirmed the role of IK1 and IKs in repolarization reserve differences. Thus, humans show greater repolarization‐delaying effects of IKr block than dogs, because of lower repolarization reserve contributions from IK1 and IKs, emphasizing species‐specific determinants of repolarization and the limitations of animal models for human disease.